Analysis of Glucose Levels in Patients Hospitalized With COVID-19 During the First Phase of This Pandemic in West Texas. (September 2020) - Rao, Sanjana; Ali, Kiran; Dennis, Jeff; Berdine, Gilbert; Test, Victor; Nugent, Kenneth
Background: Patients with hyperglycemia during hospitalization, especially during ICU hospitalizations, often have worse outcomes, even if they do not have a premorbid diagnosis of diabetes. High glucose levels can provide insight into the underlying pathogenesis of a disease and can contribute to tissue injury. Some patients with COVID-19 have hyperglycemia during hospitalizations. Methods: The Infectious Disease and Control office at University Medical Center in Lubbock, Texas, provided a list of patients with a COVID-19 infection hospitalized between March 1 and May 15, 2020. The medical records were reviewed to collect information on age, gender, history of diabetes, and glucose levels on admission and through the first 7 days of hospitalization. Results: This study included 63 patients with a mean age of 62.1 ± 14.1 years. Thirty-five patients (55.6%) were males. The in-hospital mortality rate was 30.2%. The mean admission glucose level was 129.4 ± 57.1 mg/dL in patients who survived (N = 47) and 189.6 ± 112.2 mg/dL in patients who died during hospitalization (N = 16, P  = .007). An admission glucose greater than 180 mg/dL predicted mortality in a model adjusted for a diabetes, age, and male gender. The mean differences between the maximum and minimum glucose levels calculated over the first 7 days of hospitalization were 112.93 ± 115.4 (N = 47) in patients who survived and were 240.5 ± 97.7 (N = 15) in patients who died during hospitalization ( P  = .0003). A difference between the maximum and minimum glucose level greater than 105 mg/dL was associated with increased mortality. Conclusions: Patients who died during hospitalization for COVID-19 had higher admission glucose levels than patients who survived. Larger differences between maximum and minimum glucose levels during the first 7 days of hospitalization were associated with increased mortality. These results suggest that high glucose levels identify patients at increased risk for mortality and warrant more study.